Aqueous olefin metathesis: recent developments and applications - Sabatino, Valerio; Ward, Thomas R. (Beilstein Journal of Organic Chemistry, 2019)
Olefin metathesis is one of the most powerful C–C double-bond-forming reactions. Metathesis reactions have had a tremendous impact in organic synthesis, enabling a variety of applications in polymer chemistry, drug discovery and chemical biology. Although challenging, the possibility to perform aqueous metatheses has become an attractive alternative, not only because water is a more sustainable medium, but also to exploit biocompatible conditions. This review focuses on the progress made in aqueous olefin metatheses and their applications in chemical biology.
Keywords: aqueous catalysis; artificial metalloenzymes; chemical biology; green chemistry; olefin metathesis; ruthenium catalysts; stapled peptides

Handbook of Metathesis - Grubbs, R. H.; Wenzel, A. G.; O'Leary, D. J.; Khosravi, E. (Wiley-VCH Verlag GmbH, 2015)

Alkene Metathesis in Organic Synthesis - Fürstner, A. (Springer-Verlag, 1998)

(untitled) - Ogba, O. M.; Warner, N. C.; O’Leary, D. J.; Grubbs, R. H. (Chem. Soc. Rev., 2018)

(untitled) - Herbert, M. B.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2015)

(untitled) - Fustero, S.; Simón-Fuentes, A.; Barrio, P.; Haufe, G. (Chem. Rev., 2015)

(untitled) - Olszewski, T. K.; Bieniek, M.; Skowerski, K.; Grela, K. (Synlett, 2013)

(untitled) - Olszewski, T. K.; Figlus, M.; Bieniek, M. (Chim. Oggi, 2014)

(untitled) - Hughes, D.; Wheeler, P.; Ene, D. (Org. Process Res. Dev., 2017)

Olefin Metathesis: Theory and Practice - Grela, K. (Wiley-VCH, 2014)

(untitled) - Anderson, A. W.; Merckling, M. G. (Chem. Abstr., 1956)

(untitled) - Bielawski, C. W.; Grubbs, R. H. (Prog. Polym. Sci., 2007)

(untitled) - Sinclair, F.; Alkattan, M.; Prunet, J.; Shaver, M. P. (Polym. Chem., 2017)

(untitled) - McCauley, J. A.; McIntyre, C. J.; Rudd, M. T.; Nguyen, K. T.; Romano, J. J.; Butcher, J. W.; Gilbert, K. F.; Bush, K. J.; Holloway, M. K.; Swestock, J.; Wan, B.-L.; Carroll, S. S.; et al. (J. Med. Chem., 2010)

(untitled) - Tsantrizos, Y. S.; Ferland, J.-M.; McClory, A.; Poirier, M.; Farina, V.; Yee, N. K.; Wang, X.-j.; Haddad, N.; Wei, X.; Xu, J.; Zhang, L. (J. Organomet. Chem., 2006)

(untitled) - Higman, C. S.; Lummiss, J. A. M.; Fogg, D. E. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hérisson, J.-L.; Chauvin, Y. (Makromol. Chem., 1971)

(untitled) - Casey, C. P.; Burkhardt, T. J. (J. Am. Chem. Soc., 1974)

(untitled) - Katz, T. J.; McGinnis, J. (J. Am. Chem. Soc., 1975)

(untitled) - Grubbs, R. H.; Burk, P. L.; Carr, D. D. (J. Am. Chem. Soc., 1975)

(untitled) - Grubbs, R. H.; Carr, D. D.; Hoppin, C.; Burk, P. L. (J. Am. Chem. Soc., 1976)

(untitled) - Tomasek, J.; Schatz, J. (Green Chem., 2013)

(untitled) - Burtscher, D.; Grela, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Piola, L.; Nahra, F.; Nolan, S. P. (Beilstein J. Org. Chem., 2015)

(untitled) - Skowerski, K.; Białecki, J.; Tracz, A.; Olszewski, T. K. (Green Chem., 2014)

(untitled) - Novak, B. M.; Grubbs, R. H. (J. Am. Chem. Soc., 1988)

(untitled) - Novak, B. M.; Grubbs, R. H. (J. Am. Chem. Soc., 1988)

(untitled) - Mühlebach, A.; Bernhard, P.; Bühler, N.; Karlen, T.; Ludi, A. (J. Mol. Catal., 1994)

(untitled) - Feast, W. J.; Harrison, D. B. (Polym. Bull., 1991)

(untitled) - Fürstner, A.; Ackermann, L.; Gabor, B.; Goddard, R.; Lehmann, C. W.; Mynott, R.; Stelzer, F.; Thiel, O. R. (Chem. – Eur. J., 2001)

(untitled) - Dinger, M. B.; Mol, J. C. (Organometallics, 2003)

(untitled) - Lynn, D. M.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Guidone, S.; Songis, O.; Nahra, F.; Cazin, C. S. J. (ACS Catal., 2015)

(untitled) - Levin, E.; Ivry, E.; Diesendruck, C. E.; Lemcoff, N. G. (Chem. Rev., 2015)

(untitled) - Connon, S. J.; Rivard, M.; Zaja, M.; Blechert, S. (Adv. Synth. Catal., 2003)

(untitled) - Binder, J. B.; Blank, J. J.; Raines, R. T. (Org. Lett., 2007)

(untitled) - Davis, K. J.; Sinou, D. (J. Mol. Catal. A: Chem., 2002)

(untitled) - Lipshutz, B. H.; Taft, B. R. (Org. Lett., 2008)

(untitled) - Lipshutz, B. H.; Ghorai, S.; Aguinaldo, G. T. (Adv. Synth. Catal., 2008)

(untitled) - Lipshutz, B. H.; Petersen, T. B.; Abela, A. R. (Org. Lett., 2008)

(untitled) - Lipshutz, B. H.; Aguinaldo, G. T.; Ghorai, S.; Voigtritter, K. (Org. Lett., 2008)

(untitled) - Lipshutz, B. H.; Ghorai, S.; Leong, W. W. Y.; Taft, B. R.; Krogstad, D. V. (J. Org. Chem., 2011)

(untitled) - Lipshutz, B. H.; Ghorai, S.; Cortes-Clerget, M. (Chem. – Eur. J., 2018)

(untitled) - García-Álvarez, J.; Hevia, E.; Capriati, V. (Chem. – Eur. J., 2018)

(untitled) - Pauly, J.; Gröger, H.; Patel, A. V. (Green Chem., 2018)

(untitled) - Cho, J. H.; Kim, B. M. (Org. Lett., 2003)

(untitled) - Michrowska, A.; Gułajski, Ł.; Grela, K. (Chem. Commun., 2006)

(untitled) - Vougioukalakis, G. C. (Chem. – Eur. J., 2012)

(untitled) - Wheeler, P.; Phillips, J. H.; Pederson, R. L. (Org. Process Res. Dev., 2016)

(untitled) - Skowerski, K.; Kasprzycki, P.; Bieniek, M.; Olszewski, T. K. (Tetrahedron, 2013)

(untitled) - Tracz, A.; Gawin, A.; Bieniek, M.; Olszewski, T. K.; Skowerski, K. (New J. Chem., 2018)

Q3D Elemental Impurities Guidance for Industry - U. S. Department of Health and Human Services, Food and Drug Administration (ICH, 2015)

(untitled) - Jana, A.; Grela, K. (Chem. Commun., 2018)

(untitled) - Szczepaniak, G.; Kosiński, K.; Grela, K. (Green Chem., 2014)

(untitled) - Lynn, D. M.; Kanaoka, S.; Grubbs, R. H. (J. Am. Chem. Soc., 1996)

(untitled) - Hong, S. H.; Grubbs, R. H. (J. Am. Chem. Soc., 2006)

(untitled) - Jordan, J. P.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Michrowska, A.; Gułajski, Ł.; Kaczmarska, Z.; Mennecke, K.; Kirschning, A.; Grela, K. (Green Chem., 2006)

(untitled) - Michrowska, A.; Bujok, R.; Harutyunyan, S.; Sashuk, V.; Dolgonos, G.; Grela, K. (J. Am. Chem. Soc., 2004)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Wright, D. B.; Touve, M. A.; Thompson, M. P.; Gianneschi, N. C. (ACS Macro Lett., 2018)

(untitled) - Kim, C.; Ondrusek, B. A.; Chung, H. (Org. Lett., 2018)

(untitled) - Kim, C.; Chung, H. (J. Org. Chem., 2018)

(untitled) - Schwizer, F.; Okamoto, Y.; Heinisch, T.; Gu, Y.; Pellizzoni, M. M.; Lebrun, V.; Reuter, R.; Köhler, V.; Lewis, J. C.; Ward, T. R. (Chem. Rev., 2018)

(untitled) - Rosati, F.; Roelfes, G. (ChemCatChem, 2010)

(untitled) - Lo, C.; Ringenberg, M. R.; Gnandt, D.; Wilson, Y.; Ward, T. R. (Chem. Commun., 2011)

(untitled) - Heinisch, T.; Ward, T. R. (Acc. Chem. Res., 2016)

(untitled) - Zhao, J.; Kajetanowicz, A.; Ward, T. R. (Org. Biomol. Chem., 2015)

(untitled) - Jeschek, M.; Reuter, R.; Heinisch, T.; Trindler, C.; Klehr, J.; Panke, S.; Ward, T. R. (Nature, 2016)

(untitled) - Kajetanowicz, A.; Chatterjee, A.; Reuter, R.; Ward, T. R. (Catal. Lett., 2014)

(untitled) - Matsuo, T.; Imai, C.; Yoshida, T.; Saito, T.; Hayashi, T.; Hirota, S. (Chem. Commun., 2012)

(untitled) - Mayer, C.; Gillingham, D. G.; Ward, T. R.; Hilvert, D. (Chem. Commun., 2011)

(untitled) - Grimm, A. R.; Sauer, D. F.; Davari, M. D.; Zhu, L.; Bocola, M.; Kato, S.; Onoda, A.; Hayashi, T.; Okuda, J.; Schwaneberg, U. (ACS Catal., 2018)

(untitled) - Sauer, D. F.; Bocola, M.; Broglia, C.; Arlt, M.; Zhu, L.-L.; Brocker, M.; Schwaneberg, U.; Okuda, J. (Chem. – Asian J., 2015)

(untitled) - Philippart, F.; Arlt, M.; Gotzen, S.; Tenne, S.-J.; Bocola, M.; Chen, H.-H.; Zhu, L.; Schwaneberg, U.; Okuda, J. (Chem. – Eur. J., 2013)

(untitled) - Basauri-Molina, M.; Verhoeven, D. G. A.; van Schaik, A. J.; Kleijn, H.; Klein Gebbink, R. J. M. (Chem. – Eur. J., 2015)

(untitled) - Prescher, J. A.; Bertozzi, C. R. (Nat. Chem. Biol., 2005)

(untitled) - Rossi, R. (Chim. Ind. (Milan), 1975)

(untitled) - Kuepper, F. W.; Streck, R. (Chem.-Ztg., 1975)

(untitled) - Isarov, S. A.; Pokorski, J. K. (ACS Macro Lett., 2015)

Alkene Metathesis in Organic Synthesis - Kiessling, L. L.; Strong, L. E. (Bioactive Polymers, 1998)

(untitled) - Kiessling, L. L.; Gestwicki, J. E.; Strong, L. E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Puffer, E. B.; Pontrello, J. K.; Hollenbeck, J. J.; Kink, J. A.; Kiessling, L. L. (ACS Chem. Biol., 2007)

(untitled) - Lin, Y. A.; Chalker, J. M.; Floyd, N.; Bernardes, G. J. L.; Davis, B. G. (J. Am. Chem. Soc., 2008)

(untitled) - Kodama, K.; Fukuzawa, S.; Nakayama, H.; Kigawa, T.; Sakamoto, K.; Yabuki, T.; Matsuda, N.; Shirouzu, M.; Takio, K.; Tachibana, K.; Yokoyama, S. (ChemBioChem, 2006)

(untitled) - Kodama, K.; Fukuzawa, S.; Nakayama, H.; Sakamoto, K.; Kigawa, T.; Yabuki, T.; Matsuda, N.; Shirouzu, M.; Takio, K.; Yokoyama, S.; Tachibana, K. (ChemBioChem, 2007)

(untitled) - Li, N.; Lim, R. K. V.; Edwardraja, S.; Lin, Q. (J. Am. Chem. Soc., 2011)

(untitled) - Brustad, E.; Bushey, M. L.; Lee, J. W.; Groff, D.; Liu, W.; Schultz, P. G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Hunter, L.; Condie, G. C.; Harding, M. M. (Tetrahedron Lett., 2010)

(untitled) - Bhushan, B.; Lin, Y. A.; Bak, M.; Phanumartwiwath, A.; Yang, N.; Bilyard, M. K.; Tanaka, T.; Hudson, K. L.; Lercher, L.; Stegmann, M.; Mohammed, S.; Davis, B. G. (J. Am. Chem. Soc., 2018)

(untitled) - Lu, X.; Fan, L.; Phelps, C. B.; Davie, C. P.; Donahue, C. P. (Bioconjugate Chem., 2017)

(untitled) - Toussaint, S. N. W.; Calkins, R. T.; Lee, S.; Michel, B. W. (J. Am. Chem. Soc., 2018)

(untitled) - Verdine, G. L.; Hilinski, G. J. (Methods Enzymol., 2012)

(untitled) - Blackwell, H. E.; Grubbs, R. H. (Angew. Chem., Int. Ed., 1998)

(untitled) - Walensky, L. D.; Kung, A. L.; Escher, I.; Malia, T. J.; Barbuto, S.; Wright, R. D.; Wagner, G.; Verdine, G. L.; Korsmeyer, S. J. (Science, 2004)

(untitled) - Moellering, R. E.; Cornejo, M.; Davis, T. N.; Del Bianco, C.; Aster, J. C.; Blacklow, S. C.; Kung, A. L.; Gilliland, D. G.; Verdine, G. L.; Bradner, J. E. (Nature, 2009)

(untitled) - Bernal, F.; Wade, M.; Godes, M.; Davis, T. N.; Whitehead, D. G.; Kung, A. L.; Wahl, G. M.; Walensky, L. D. (Cancer Cell, 2010)

(untitled) - Meric-Bernstam, F.; Saleh, M. N.; Infante, J. R.; Goel, S.; Falchook, G. S.; Shapiro, G.; Chung, K. Y.; Conry, R. M.; Hong, D. S.; Wang, J. S.-Z.; Steidl, U.; Walensky, L. D.; et al. (J. Clin. Oncol., 2017)